MOTIVASI SISWA SMKN 4 MENGIKUTI PROGRAM MENABUNG DI BANK SAMPAH DALANG COLLECTION KOTA PEKANBARU - Yulianti, Eva; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at SMK Negeri 4 Kota Pekanbaru. The purpose of this research was to find out the characteristics and motivation of students taking part in a savings program at the Dalang Collection Garbage Bank. The focus topic of this research is the motivation of students to join the savings program at the Pekanbaru Dalang Collection Garbage Bank. This study uses the Rendom Sampling Technique in Sampling. Respondents in this study were students of SMK Negeri 4 Pekanbaru who were actively saving at the Dalang Collection Garbage Bank of which there were 57 people. This research uses quantitative methods with observation instruments, questionnaires and documentation. The researchers found that in this study: (a) Overall respondents or 100% of respondents had a high level of awareness to save the environment from waste (b) Level of Motivation for students Self-study early on by participating in the "High" Garbage Bank Program with a percentage of 50.9% (c) Motivation levels of students form innovative self-character by participating in the "Low" Garbage Bank Program with a percentage of 52.6%.Â Keywords: Motivation, Garbage BankÂ